Some Aspects of the Application of Traditional and Modern Mapping Methods in the Preparation of Digital Maps - Nodirjon Najmiddinovich Rakhimov; Zulkhumor Mukhtarovna Umarova; Farrukh Azamatovich Ma'mirov (International Journal on Integrated Education, 2022)
The article it is discussed some aspects of the application of traditional and modern mapping methods in the preparation of digital maps, because the field of hydrogeological, engineering-geological and geoecological works is a combination of natural, natural-man-made and man-made objects of the geological environment, interconnected by information features and properties.